Efficacy of avian radar systems for tracking birds on the airfield of a large international airport. (21st September 2018) - Phillips, Adam C.; Majumdar, Siddhartha; Washburn, Brian E.; Mayer, David; Swearingin, Ryan M.; Herricks, Edwin E.; Guerrant, Travis L.; Beckerman, Scott F.; Pullins, Craig K.
ABSTRACT: Avian radar technologies have the potential to serve an important role in the quantification of bird movements and determining patterns of bird use in areas where human–wildlife conflicts might occur (e.g., airports, wind‐energy facilities). However, capabilities and limitations of these technologies are relatively unknown and ground‐truthing studies are needed to help wildlife managers understand the biological meaning of radar information. We evaluated the efficacy of 3 X‐band marine radar sensors for tracking birds and flocks of birds observed on the airfield at Chicago's O'Hare International Airport, USA, during March 2011–November 2012. We used specific information regarding field observations of birds or flocks to determine how frequently the 3 radar sensors provided corresponding tracks of these avian targets. In addition, we examined various factors to determine if they had any influence on the frequency of correspondence between visual observations and radar tracks. Of the 972 sightings of individual birds (49%) or flocks of birds (51%) by observers on the airfield that had the potential to be observed by the radar, 143 (15%) were tracked by ≥1 radar sensor. All confirmed tracks of individual birds or flocks were ≤4.8 km from these radars. Among the 3 radar sensors, larger bodied bird species, bird/flocks flying at higher altitudes, and bird/flocks closer to the radars increased the ability of those units to track avian targets. This study provides new information regarding the performance of radar systems for tracking birds on the airfield of one of the largest and busiest airports in the world. Published 2018. This article is a U.S. Government work and is in the public domain in the USA. Abstract : Avian radar systems have the potential to quantify bird movement patterns, although much remains unknown about this technology. We determined the efficacy of 3 avian radars (used simultaneously) in a complex airport environment. Several factors, including bird species, avian target altitude, and distance from the radars, influenced the ability of the radars to detect and track individual birds and flocks.